Consensus on potential biomarkers developed for use in clinical tests for schizophrenia. Issue 1 (23rd February 2022) - Lin, Ping; Sun, Junyu; Lou, Xiaoyan; Li, Dan; Shi, Yun; Li, Zhenhua; Ma, Peijun; Li, Ping; Chen, Shuzi; Jin, Weifeng; Liu, Shuai; Chen, Qing; et al.
Abstract : Background: Schizophrenia is a serious mental illness affecting approximately 20 million individuals globally. Both genetic and environmental factors contribute to the illness. If left undiagnosed and untreated, schizophrenia results in impaired social function, repeated hospital admissions, reduced quality of life and decreased life expectancy. Clinical diagnosis largely relies on subjective evidence, including self-reported experiences, and reported behavioural abnormalities followed by psychiatric evaluation. In addition, psychoses may occur along with other conditions, and the symptoms are often episodic and transient, posing a significant challenge to the precision of diagnosis. Therefore, objective, specific tests using biomarkers are urgently needed for differential diagnosis of schizophrenia in clinical practice. Aims: We aimed to provide evidence-based and consensus-based recommendations, with a summary of laboratory measurements that could potentially be used as biomarkers for schizophrenia, and to discuss directions for future research. Methods: We searched publications within the last 10 years with the following keywords: 'schizophrenia', 'gene', 'inflammation', 'neurotransmitter', 'protein marker', 'gut microbiota', 'pharmacogenomics' and 'biomarker'. A draft of the consensus was discussed and agreed on by all authors at a round table session. Results: We summarised the characteristics of candidate diagnostic markers for schizophrenia, including genetic, inflammatory, neurotransmitter, peripheral protein, pharmacogenomic and gut microbiota markers. We also proposed a novel laboratory process for diagnosing schizophrenia in clinical practice based on the evidence summarised in this paper. Conclusions: Further efforts are needed to identify schizophrenia-specific genetic and epigenetic markers for precise diagnosis, differential diagnosis and ethnicity-specific markers for the Chinese population. The development of novel laboratory techniques is making it possible to use these biomarkers clinically to diagnose disease.